Influence of vacuum activated diffusion chroming on mechanical properties of the surface of steel 25X1MF - Rudenkyi, S.G.; Zmij, V.I.; Kartzev, N.F.; Korneev, A.A.; Kunchenko, A.V.; Kunchenko, V.V.; Kunchenko, Y.V.; Marinin, V.G.; Kovalenko, V.I.; Bortnytska, M.O.; Ryzhova, T.P.; Lashenko, I.A. (Вопросы атомной науки и техники, 2020)
In the work, the surface of samples made of 25X1MF steel was saturated with chromium. For this, the method of vacuum activated diffusion chromium plating was used. In this process, sodium chloride was used as an activator. It was found that vacuum activated diffusion chromium plating of samples made of 25Kh1MF steel leads to the formation of a surface layer containing from 87 to 97 wt.% of this element. It was found that an increase in the temperature of the process and its duration leads to an increase in the chromium content on the surface of the samples. The tests showed that in the case of cavitations-erosion effects on the surface of chrome-plated samples of steel 25X1MF they have higher resistance. With abrasive wear, the resistance of the chrome-plated steel surface is 1.8 to 3 times higher compared to untreated material. Проведено насичення поверхні зразків зі сталі 25Х1МФ хромом. Для цього використовували метод вакуумного активованого дифузійного хромування. У цьому процесі в якості активатора використовували хлористий натрій. Було встановлено, що вакуумне активоване дифузійне хромування зразків зі сталі 25Х1МФ призводить до формування поверхневого шару, що містить від 87 до 97 мас.% цього елемента. При цьому встановлено, що підвищення температури процесу і його тривалості призводить до збільшення вмісту хрому на поверхні зразків. Проведені випробування показали, що в разі кавітаційно-ерозійного впливу на поверхню хромованих зразків зі сталі 25Х1МФ вони мають більш високу стійкість. При абразивному зносі стійкість хромованої поверхні сталі в 1,8–3 рази вище в порівнянні з необробленим матеріалом. Проведено насыщение поверхности образцов из стали 25Х1МФ хромом. Для этого использовали метод вакуумного активированного диффузионного хромирования. В этом процессе в качестве активатора использовали хлористый натрий. Было установлено, что вакуумное активированное диффузионное хромирование образцов из стали 25Х1МФ приводит к формированию поверхностного слоя, содержащего от 87 до 97 вес.% этого элемента. При этом установлено, что повышение температуры процесса и его длительности приводит к увеличению содержания хрома на поверхности образцов. Проведенные испытания показали, что в случае кавитационно-эрозионного воздействия на поверхность хромированных образцов из стали 25Х1МФ они имеют более высокую стойкость. При абразивном износе стойкость хромированной поверхности стали в 1,8–3 раза выше по сравнению с необработанным материалом.